Step
*
2
1
of Lemma
simple_more_general_fan_theorem
1. T : ℕ ⟶ Type
2. ∀i:ℕ. T[i]
3. ∀i:ℕ. ∀K:T[i] ⟶ ℕ.  (∃B:ℕ [(∀t:T[i]. ((K t) ≤ B))])
4. X : n:ℕ ⟶ (i:ℕn ⟶ T[i]) ⟶ ℙ
5. ∀f:i:ℕ ⟶ T[i]. (↓∃n:ℕ. X[n;f])
6. ∀n:ℕ. ∀s:i:ℕn ⟶ T[i].  Dec(X[n;s])
7. n : ℕ
8. s : ℕn ⟶ (i:ℕ × T[i])
9. ∀i:ℕn. ((fst((s i))) = i ∈ ℤ)
10. X[n;project-seq(s)]
11. f : ℕ ⟶ (i:ℕ × T[i])
12. ∀i:ℕ. ((fst((f i))) = (i + n) ∈ ℤ)
⊢ X[n + 0;project-seq(seq-append(n;0;s;f))]
BY
{ ((NthHypEq (-3) THEN EqCD) THEN Auto)⋅ }
1
.....subterm..... T:t
2:n
1. T : ℕ ⟶ Type
2. ∀i:ℕ. T[i]
3. ∀i:ℕ. ∀K:T[i] ⟶ ℕ.  (∃B:ℕ [(∀t:T[i]. ((K t) ≤ B))])
4. X : n:ℕ ⟶ (i:ℕn ⟶ T[i]) ⟶ ℙ
5. ∀f:i:ℕ ⟶ T[i]. (↓∃n:ℕ. X[n;f])
6. ∀n:ℕ. ∀s:i:ℕn ⟶ T[i].  Dec(X[n;s])
7. n : ℕ
8. s : ℕn ⟶ (i:ℕ × T[i])
9. ∀i:ℕn. ((fst((s i))) = i ∈ ℤ)
10. X[n;project-seq(s)]
11. f : ℕ ⟶ (i:ℕ × T[i])
12. ∀i:ℕ. ((fst((f i))) = (i + n) ∈ ℤ)
⊢ project-seq(seq-append(n;0;s;f)) = project-seq(s) ∈ (i:ℕn + 0 ⟶ T[i])
Latex:
Latex:
1.  T  :  \mBbbN{}  {}\mrightarrow{}  Type
2.  \mforall{}i:\mBbbN{}.  T[i]
3.  \mforall{}i:\mBbbN{}.  \mforall{}K:T[i]  {}\mrightarrow{}  \mBbbN{}.    (\mexists{}B:\mBbbN{}  [(\mforall{}t:T[i].  ((K  t)  \mleq{}  B))])
4.  X  :  n:\mBbbN{}  {}\mrightarrow{}  (i:\mBbbN{}n  {}\mrightarrow{}  T[i])  {}\mrightarrow{}  \mBbbP{}
5.  \mforall{}f:i:\mBbbN{}  {}\mrightarrow{}  T[i].  (\mdownarrow{}\mexists{}n:\mBbbN{}.  X[n;f])
6.  \mforall{}n:\mBbbN{}.  \mforall{}s:i:\mBbbN{}n  {}\mrightarrow{}  T[i].    Dec(X[n;s])
7.  n  :  \mBbbN{}
8.  s  :  \mBbbN{}n  {}\mrightarrow{}  (i:\mBbbN{}  \mtimes{}  T[i])
9.  \mforall{}i:\mBbbN{}n.  ((fst((s  i)))  =  i)
10.  X[n;project-seq(s)]
11.  f  :  \mBbbN{}  {}\mrightarrow{}  (i:\mBbbN{}  \mtimes{}  T[i])
12.  \mforall{}i:\mBbbN{}.  ((fst((f  i)))  =  (i  +  n))
\mvdash{}  X[n  +  0;project-seq(seq-append(n;0;s;f))]
By
Latex:
((NthHypEq  (-3)  THEN  EqCD)  THEN  Auto)\mcdot{}
Home
Index